I dont know how to do the signals so ill right in words everything....
(1-1)^n = n SIGMA k=0 nCk * 1^k *(-1)^(n-k)
why does it equals to:
n SIGMA k=0 nCk * (-1)^k
i dont understand why (-1)^(n-k) become (-1)^k
someone can help me please???
I dont know how to do the signals so ill right in words everything....
(1-1)^n = n SIGMA k=0 nCk * 1^k *(-1)^(n-k)
why does it equals to:
n SIGMA k=0 nCk * (-1)^k
i dont understand why (-1)^(n-k) become (-1)^k
someone can help me please???
The following expansion can be written in two ways.
Note the placement of the exponents in the equivalent sums.
$\displaystyle \left( {a + b} \right)^n = \sum\limits_{k = 0}^n {{n \choose k}\left( a \right)^k \left( b \right)^{n - k} } \;\text{OR} \,\sum\limits_{k = 0}^n {{n \choose k}\left( a \right)^{n - k} \left( b \right)^k } $